ANALISIS PREDIKSI KEBANGKRUTAN MODEL ZMIJEWSKI DAN MODEL OHLSON PADA BADAN USAHA MILIK NEGARA (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014 – 2018 - Inneke Ryan Saputri; Bambang Widarno; Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The purpose of this research is to analyze the most accuratebankruptcy prediction model between the Zmijewski and Ohlson models inpredicting the bankruptcy of BUMN companies listed on the IDX on 2014 to 2018.The sample used is 16 BUMN with purposive sampling method. The data analysismethod uses the Zmjewski model and the Ohlson model with the help of MicrosoftExcel 2010. The results of this study are the Zmijewskizmodel is the most accuratemodelzin predicting bankruptcyzof BUMN companies listedzon thezIDX for the2014-2018 periodzwith an accuracy rate of 60% and type error. 40% while theOhlson model has an accuracy rate of 16.25% and a type error of 83.75%.